Aplikasi Pendidikan Dan Pelatihan Koperasi Di Koperasi Simpan Pinjam Bada Lestari - I Ketut Santa Wijaya; Cokorda Rai Adi Pramartha; I Gede Surya Rahayuda (Jurnal Pengabdian Informatika, 2024)
In an era of ever-evolving technology, using applications has become an integral part of our daily lives. Information technology plays an important role in human life, especially in the field of small and medium enterprises such as cooperatives. However, co-operative development remains stagnant, with only 13% of all co-operatives having digital systems in place. This study therefore aims to develop an educational and training application for co-operative members to improve their knowledge and skills on co-operative principles and related undertakings. Through this application, cooperatives are expected to improve the accessibility, effectiveness and efficiency of their members' education, thereby increasing awareness of cooperative principles and the sustainability of cooperative activities as a whole.